The Rafī’ee-Qazvīnī's Solution to the Sadrāian Problem of Return - Mohammad Kazem Forghani; Mohammad Ahmadizadeh (پژوهشنامه فلسفه دین, 2013)
According to the principles of transcendent philosophy (Al-Hikmat Al-Mutaāliyah), the human soul as a contingent existence after being created in this world (Hoduth) has a continuous motion from an actuality (Fi’liyyah) to another one until becoming immaterial (Mujarrad). This means that he leaves his body and continues to his evolution immaterially. According to the principle of “Impossibility of Return” (Imtinā’-i-Tarāju’) it seems impossible for human being to return to the mundane life after his death. This belief is apparently inconsistent with the Islamic doctrine of “dead human beings’ return to the life” (Raj’ah). So, since transcendent philosophers reject the doctrine of reincarnation on the basis of the principle of “Impossibility of Return”, they should explain the doctrine of Raj’ah in a consistent way. Sayyed Abolhasan Rafī’ee-Qazvīnī is one of the few transcendent philosophers who have taken this issue into account. Although he validates the principle of Impossibility of Return, he asserts that it does not include the doctrine of Raj’ah. He tries to defend the doctrine of Raj’ah and differentiate it from the doctrine of reincarnation through a couple of philosophical principles. For example he accepts that Coercion does not last (قسر دائمی نیست) and every existent has its exclusive existential influence which is necessarily emergent (هر موجود، اثر وجودی لازم البروز خاصّ خود را دارد).